An Econometric Analysis of Interstate Migration in Peninsular Malaysia - Ayob, Ahmad Mahdzan (1979)
An econometric model is used to explain inter-stat migration in Peninsular Malaysia using the 1957 population census data. The determinants of interstate migration are the size of employment in the secondary and tertiary industries at the destination, the size of the population at the origin, distance between the two points, and a dummy variable indicating whether states share a common boundary and traversed by a road or railway.